Age- and Gender-Specific Time Trend in Risk of Death of Patients Admitted with Aneurysmal Subarachnoid Hemorrhage in the Netherlands. (October 2013) - Nieuwkamp, Dennis J.; Vaartjes, Ilonca; Algra, Ale; Bots, Michiel L.; Rinkel, Gabriël J. E.
Background and aim: In a meta-analysis of population-based studies, case-fatality rates of subarachnoid hemorrhage have decreased worldwide by 17% between 1973 and 2002. However, age- and gender-specific decreases could not be determined. Because >10% of patients with subarachnoid hemorrhage die before reaching the hospital, this suggests that the prognosis for hospitalized subarachnoid hemorrhage patients has improved even more. We assessed age- and gender-specific time trends of the risk of death for hospitalized subarachnoid hemorrhage patients. Methods: From the Dutch hospital discharge register (nationwide coverage), we identified 9403 patients admitted with subarachnoid hemorrhage in the Netherlands between 1997 and 2006. Changes in risk of death within this time frame and influence of age and gender were quantified with Poisson regression. Results: The overall 30-day risk of death was 34·0% (95% confidence interval 33·1↔35·0%). After adjustment for age and gender, the annual decrease was 1·6% (95% confidence interval 0·5↔2·6%), which confers to a decrease of 13·4% (95% confidence interval4·8↔21·2%) in the study period. The one-year risk of death decreased 2·0% per year (95% confidence interval1·1↔2·9%). The decrease in risk of death was mainly found in the period 2003–2005, was not found for patients ≥65 years and was statistically significant for men, but not for women. Conclusions: The decrease in risk of death for patients admitted in the Netherlands with subarachnoid hemorrhage is overall considerable, but unevenly distributed over age and gender. Further research should focus on reasons for improved survival (improved diagnostics, improved treatment) and reasons why improvement has not occurred for women and for patients in older age categories.